1998
DOI: 10.1074/jbc.273.34.21648
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Properties of Two Cysteine Proteinases (Gingipains R), the Products of Two Related but Individual Genes ofPorphyromonas gingivalis

Abstract: Proteolytic enzymes produced by Porphyromonas gingivalis are important virulence factors of this periodontopathogen. Two of these enzymes, referred to as arginine-specific cysteine proteinases (gingipains R), are the product of two related genes. Here, we describe the purification of an enzyme translated from the rgpB/rgp-2 gene (gingipain R2, RGP-2) and secreted as a single chain protein of 422 residues. The enzyme occurs in several isoforms differing in pI, molecular mass, mobility in gelatin zymography gels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
189
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 156 publications
(201 citation statements)
references
References 51 publications
10
189
1
Order By: Relevance
“…lation product is a single protein with a primary structure essentially identical to the catalytic domain of HRgpA (30,31). Despite both a structural similarity and a specificity restricted to Arg-Xaa peptide bonds, HRgpA and RgpB show considerable differences in catalytic potency (26) which is most profoundly manifested in their ability to activate factor X (32) and protein C (33). In addition to activation of these members of the coagulation cascade pathway, it was also shown that RgpB was capable of generating kallikrein from plasma prekallikrein (16).…”
Section: S534 -S536) Our Results Indicate That Bacterial Proteimentioning
confidence: 99%
See 1 more Smart Citation
“…lation product is a single protein with a primary structure essentially identical to the catalytic domain of HRgpA (30,31). Despite both a structural similarity and a specificity restricted to Arg-Xaa peptide bonds, HRgpA and RgpB show considerable differences in catalytic potency (26) which is most profoundly manifested in their ability to activate factor X (32) and protein C (33). In addition to activation of these members of the coagulation cascade pathway, it was also shown that RgpB was capable of generating kallikrein from plasma prekallikrein (16).…”
Section: S534 -S536) Our Results Indicate That Bacterial Proteimentioning
confidence: 99%
“…From the culture medium of P. gingivalis HG66 we have purified previously two major forms of arginine-specific cysteine proteinases, HRgpA 1 and RgpB, formerly referred to as high molecular mass gingipain R (95-kDa gingipain R1 or HRGP) and 50-kDa gingipain R2 (RGP-2), respectively (24,26). Both of these enzymes are products of two distinct but related genes (27).…”
Section: S534 -S536) Our Results Indicate That Bacterial Proteimentioning
confidence: 99%
“…The separated proteins were then transferred to BioTrace nitrocellulose membranes (Pall Corporation) and processed at 15 V for 25 min with a Semi-Dry Trans-blot apparatus (Bio-Rad). The blots were probed with gingipain-specific antibodies (Potempa et al, 1998). The secondary antibody used was immunoglobulin G (heavy plus light chains)-horseradish peroxidase conjugate (Zymed Laboratories).…”
Section: Methodsmentioning
confidence: 99%
“…Inactivation through autocatalytic processing also occurred during purification under ordinary conditions. We attempted to reversibly inhibit the Clp activity with inhibitors such as EDTA and 4,49-dithiopyridine disulfide (Potempa et al, 1998), but we failed to fully restore the Clp activity by incubation in the activation buffer (data not shown). Another characteristic feature of Clp is that it is easily denatured into insoluble aggregates unless a high ionic strength buffer (0.15 M or higher NaCl) is used.…”
Section: Discussionmentioning
confidence: 99%